2015
DOI: 10.1016/j.bbamcr.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

mTor mediates tau localization and secretion: Implication for Alzheimer's disease

Abstract: Abnormally hyperphosphorylated tau aggregates form paired helical filaments (PHFs) in neurofibrillary tangles, a key hallmark of Alzheimer's disease (AD) and other tauopathies. The cerebrospinal fluid (CSF) levels of soluble total tau and phospho-tau from clinically diagnosed AD patients are significantly higher compared with controls. Data from both in vitro and in vivo AD models have implied that an aberrant increase of mammalian target of rapamycin (mTor) signaling may be a causative factor for the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 64 publications
2
85
0
Order By: Relevance
“…Hyper-activation of mTOR following high energy food intake has been shown to be associated with increased systemic inflammation, and result in insulin resistance through the phosphorylation of p70S6K [20] in animal models. Further, pathological hyper-activation of mTORC1, specifically the levels of p-mTOR and its downstream targets, including p-p70S6K, have been reported to be higher in the brains of Alzheimer’s Disease (AD) clinical samples and mouse models [21-28] of neurodegenerative disease. These studies suggest an association between obesity and activation of mTOR pathway to neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Hyper-activation of mTOR following high energy food intake has been shown to be associated with increased systemic inflammation, and result in insulin resistance through the phosphorylation of p70S6K [20] in animal models. Further, pathological hyper-activation of mTORC1, specifically the levels of p-mTOR and its downstream targets, including p-p70S6K, have been reported to be higher in the brains of Alzheimer’s Disease (AD) clinical samples and mouse models [21-28] of neurodegenerative disease. These studies suggest an association between obesity and activation of mTOR pathway to neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Tau interacts with several proteins in the Akt and mTOR signaling cascades, including Akt [35, 36], ribosomal protein S6 kinase beta-1 (p70S6K) [37, 38], mTOR [39, 40], phosphatase and tensin homolog (PTEN) [41, 42], glycogen synthase kinases 3 alpha and beta (GSK3α, GSK3β) [43-46], and many others, leading to actions such as tau phosphorylation and degradation. For example, GSK3β is known to phosphorylate tau at numerous sites [45].…”
Section: Resultsmentioning
confidence: 99%
“…In this context, Tang et al have shown that mTOR overexpression or the lack of its expression is responsible for the altered balance of phosphorylated/non phosphorylated tau, a condition which might facilitate tau deposition [59]. In the brain, the kinase mTOR has been shown to control molecular functions related to cell cycle regulation, A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 9 cell death and several metabolic pathways.…”
Section: Accepted Manuscriptmentioning
confidence: 98%